IMPROVING MATHEMATICS LEARNING PROCESSES AND OUTCOMES USING THE REALISTIC MATHEMATICS EDUCATION MODEL IN GRADE IV SDN 027/II SUNGAI ARANG - anggi putri hania; Randi Eka Putra; Sundahry Sundahry (Prima: Jurnal Pendidikan Matematika, 2026)
This research was motivated by the low mathematics learning process and outcomes at SDN 027/II Sungai Arang due to the lack of optimization of learning models and material contextuality. This Classroom Action Research (CAR) aims to improve the quality of learning through the Realistic Mathematics Education model. Implemented in two cycles with stages of planning, action, observation, and reflection, the research involved 15 fourth-grade students. The results show that the application of the RME model by utilizing real-world contexts creates a meaningful and interactive learning atmosphere. A significant increase is seen in the classical completion rate which increased from 53% in Cycle I to 87% in Cycle II, exceeding the target indicator of 80%. It is concluded that the RME model is effective in improving the mathematics learning process and outcomes by linking concepts to everyday life situations.